Analysis of Self-Efficacy and Characteristics of Patients with Chronic Kidney Disease Underwent Hemodialysis - Rahma Edy Pakaya; Yuliana Syam; Syahrul Syahrul (Jurnal Keperawatan, 2021)
Introduction: Increased awareness and understanding of the overall burden of CKD is required in managing disease independently. Self-efficacy can support self-management behavior. Objectives:  This study aims to determine the self-efficacy of patients with chronic kidney disease undergoing hemodialysis based on patient characteristics. Method: This study used an analytic survey method with a cross-sectional study approach. Sampling with purposive sampling with a sample size of 80 people. Data were analyzed with Mann Whitney, Kruskall-Wallis, Spearman Correlation depending on the type of data available with a confidence level of 95%. Results: The results of self-efficacy analysis based on the characteristics of patients with chronic kidney disease undergoing hemodialysis found that there was a correlation between the length of HD and the patient's self-efficacy (p: 0.008) where the patient's self-efficacy would increase along with the addition of the patient's HD duration (r: 0.293). As for age, number of comorbidities, gender, education, marriage status, employment, financing, religious activities, social activities, blood pressure, and body weight were not related to patient self-efficacy (p> 0.05). Conclusion: Patient self-efficacy related to blood pressure. As for age, a number of comorbidities, gender, education, marriage status, employment, financing, religious activities, social activities, length of HD, and body weight were not related to patient self-efficacy.